The association of gene rearrangement and lymphoma diagnosis: A prospective observational study. Issue 24 (12th June 2020) - He, Xiaoyan; Xu, Pei; Wang, Xianwei; Jiang, Shuming; Gong, Daoyin; Wu, Ning
Abstract: Introduction: To investigate the gene rearrangement and mutation of lymphoma biomarkers including (Immunoglobulin H (IgH), Immunoglobulin kappa (IGK), Immunoglobulin lambda (IGL), and TCR) in the lymphoma diagnosis. Methods and analysis: Paraffin tissue samples from 240 cases diagnosed as suspected lymphoma in the department of pathology, Deyang City People's Hospital from June 2020 to June 2021 will be enrolled. Deoxyribonucleic acid extraction and Polymerase Chain Reaction (PCR) amplification will be performed in these paraffin tissue samples. Immunoglobulin and T cell receptor (TCR) rearrangement will be analyzed by hetero-double chain gel electrophoresis and BioMed-2 standardized immunoglobulin gene rearrangement detection system. In this study protocol IGH gene rearrangement, IGK gene rearrangement, both IGH and IGL gene rearrangement, both IGH and IGK gene rearrangement, both IGK and IGL gene rearrangement, both IGH, IGK and IGL gene rearrangement, TCR gene rearrangement and positive Ig/TCR rearrangement will be analyzed. Discussion: In this study, we will use B and T cell lymphoma analysis focusing on IgH, IGK, IGL, and TCR gene rearrangement, so as to provide early guidance for the diagnosis of lymphoma. Second generation sequencing technology is helpful in the differential diagnosis of lymphoma. Trial registration: Chinese Clinical trial registry: ChiCTR2000032366.